Pelaksanaan Kode Etik Pustakawan Untuk Memaksimalkan Kualitas Layanan Perpustakaan SMP Negeri 1 Sumberrejo - Dede Meiliya Ariani (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
ABSTRACTThe librarian's code of ethics is the key to customer service satisfaction. Professional librarians must have high integrity with the ability and expertise of their field and have a personality by the values of the professional code of ethics. Purpose Research. This study aimed to determine the application of the librarian's code ethics in the library of SMP Negeri 1 Sumberrejo in serving the users and explain what obstacles were experienced by librarians in implementing the librarian's code ethics. Methods. The qualitative approach is the method used in this research. Data collection techniques using interviews, observation, and documentation. Two informants were interviewed, namely the head of the library and the librarian. Result. The result of this research is that application of the librarian's code ethics in the SMP Negeri 1 Sumberrejo is still not optimal. The librarian's response is not good when communicating with the users in providing services, and the librarian is not firm when library facilities are misused. Conclusion. Librarians still face obstacles from internal factors, and librarians do not understand the librarian's code of ethics and the varying level of librarian education. External factors are the lack of socialization regarding the librarian's code of ethics and the lack of strict sanctions violating the code of ethics. Keywords: Code of Ethics; Librarian; School Library